Ground Fault Line Selection with Improved Residual Flow Incremental Method - Wenhong Li; Tingqiang Guan; Xueguang Qi; Gonghua Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
According to the shortcoming of single-phase ground fault line selection method in the resonant grounded system such as the uncertainty of its device by fast compensation with the automatic compensation equipment, an arc suppression and residual flow incremental method is proposed to effectively choose the earth fault line. Firstly, when the single-phase ground fault occurs, the arc suppression coil parameters are adjusted to realize compensation and arc suppression. Then the arc suppression coil inductance values are modulated to make the zero-sequence current of fault line changed, at the same time, the zero-sequence current value is detected and its change will be captured to select the fault line. The simulation experiments prove that the arc grounding over voltage damage can be effectively reduced by arc suppression coil full compensation and fault line can be effectively selected by arc suppression and residual flow increment method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3106